2012
DOI: 10.1038/msb.2012.11
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptomics of pathogenic and non‐pathogenic Listeria species

Abstract: Comparative RNA-seq analysis of two related pathogenic and non-pathogenic bacterial strains reveals a hidden layer of divergence in the non-coding genome as well as conserved, widespread regulatory structures called ‘Excludons', which mediate regulation through long non-coding antisense RNAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
311
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 263 publications
(334 citation statements)
references
References 50 publications
21
311
1
1
Order By: Relevance
“…Coordinate regulation of overlapping transcripts from divergently transcribed genes has been described in S. aureus and Listeria monocytogenes (11,25). Lasa et al (9) reported involvement of RNase III in the formation of short RNA fragments (∼22 nt) mapping to overlapping transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…Coordinate regulation of overlapping transcripts from divergently transcribed genes has been described in S. aureus and Listeria monocytogenes (11,25). Lasa et al (9) reported involvement of RNase III in the formation of short RNA fragments (∼22 nt) mapping to overlapping transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…In both Listeria monocytogenes and Staphylococcus aureus a subset of asRNAs are dependent on the alternative sigma factor SigB, suggesting these transcripts are regulated and functional. 20,22 In a recent report, 67 bona fide asRNAs were co-immunoprecipitated with the RNA chaperone Hfq in E. coli. 7 Hfq is often required for the function of trans-encoded sRNAs in Gram-negative bacteria, but its role in gene regulation via cis-encoded asRNAs was not previously reported.…”
Section: Evidence For Functional Asrnasmentioning
confidence: 99%
“…The first noncoding RNAs (ncRNAs) in L. monocytogenes were identified by coimmunoprecipitation with Hfq, a small RNA-binding protein required for the activity of small regulatory RNAs in prokaryotes [21] and by an in silico-based approaches [22]. Since then, the use of high-density tiling arrays and RNA deep sequencing provided a picture of the whole L. monocytogenes transcriptome in multiple conditions, allowing the discovery of many regulatory RNAs [23][24][25][26][27][28] and the annotation of hundreds of regulatory RNAs in L.…”
Section: Unconventional Mechanisms Regulating Bacterial Gene Expressimentioning
confidence: 99%
“…An excludon typically consists of two divergent transcriptional units overlapped by a long asRNA that inhibits the expression of one of the two divergent operons, but whose distal part harbors information as an mRNA, activating therefore the expression of the other operon ( Figure 3C). The first excludon discovered was the mogR locus in L. monogytogenes and excludons are conserved in other Listeria species 11 and also in a more distantly related bacterium Clostridium difficile [28]. It is highly possible that excludons exist not only in bacteria, but also in other organisms.…”
mentioning
confidence: 99%
See 1 more Smart Citation